2014
DOI: 10.11130/jei.2014.29.4.700
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Volatility and Tourist Flows into Turkey

Abstract: This paper examines the effects of Exchange Rate Volatility on tourist flows into Turkey for the period of 1994~2012. Our results show that (i) there is a negative relationship between exchange rate volatility and tourist inflows into Turkey; (ii) there is a negative impact of the relative price ratio on the tourist flows indicating that relatively expensive places deter tourist arrivals, given the keen international competition among alternative destinations; (iii) GDP per capita at tourist origin, measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…It is vital to understand, that the effects of exchange rate volatility on tourist arrivals depended on whether tourists were risk-averse or risk-lovers. Exchange rate volatility has a negative impact on the decision to travel for risk-averse tourists and, due to lower arrivals, has a positive impact on risk-seeking tourists because it is seen as a chance for making some profits; therefore, leads to higher arrivals (Agiomirgianakis et al, 2014). (CAPMAS, 2018).…”
Section: The Relationship Between Exchange Rate Changes and Internatimentioning
confidence: 99%
“…It is vital to understand, that the effects of exchange rate volatility on tourist arrivals depended on whether tourists were risk-averse or risk-lovers. Exchange rate volatility has a negative impact on the decision to travel for risk-averse tourists and, due to lower arrivals, has a positive impact on risk-seeking tourists because it is seen as a chance for making some profits; therefore, leads to higher arrivals (Agiomirgianakis et al, 2014). (CAPMAS, 2018).…”
Section: The Relationship Between Exchange Rate Changes and Internatimentioning
confidence: 99%
“…Agiomirgianakis et al (2014) used quarterly data between 1994 and 2012 in their study on exchange rate volatility and tourist flows in Turkey. There was a negative relationship between exchange rate volatility and tourist flows in the paper.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The model for examining the effect of exchange rate volatility on tourist flows is used also by Agiomirgianakis et al (2014) to examine the effect of exchange rate volatility on tourist flows. In this paper, the data for the period between the first quarter of 2003 and the first quarter of 2016 is used.…”
Section: The Modelmentioning
confidence: 99%
“…Changes in the currency rates are seen to have an impact on the total international travel costs of individuals. There are few studies conducted on the relationship between exchange rates and tourism demand in Turkey (Agiomirgianakis et al, 2014;Akay, 2017;Özcan & Uçak, 2016). Agiomirgianakis et al (2014) found that exchange rate volatility is negatively associated with the tourist inflow to Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies conducted on the relationship between exchange rates and tourism demand in Turkey (Agiomirgianakis et al, 2014;Akay, 2017;Özcan & Uçak, 2016). Agiomirgianakis et al (2014) found that exchange rate volatility is negatively associated with the tourist inflow to Turkey. Meanwhile, the research by (Kiliç & Bayar, 2014) for the period between 1994 and 2013 have found the effective exchange rates to be positively related to tourism acceptance and travel expenditures in that particular country.…”
Section: Introductionmentioning
confidence: 99%